Animal farm - Orwell, George (Lahore Ilqa Publication, 2014)
When the downtrodden animals of Manor Farm overthrow their master Mr Jones and take over the farm themselves, they imagine it is the beginning of a life of freedom and equality. But gradually a cunning, ruthless elite among them, masterminded by the pigs Napoleon and Snowball, starts to take control.
Originally Published: London: Secker & Warburg, 1945.
Keywords: Satire -- Fables -- Totalitarianism